Utilizing Web Engineering to Build a Savings and Loans Information System in A Plasma Pratama Mandiri Cooperative - Miranti, Amelia Tya; Fatoni, Fatoni; Andri, Andri; Erlansyah, Deni (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
The Plasma Pratama Mandiri Cooperative operates in the field of savings and loan fund services for its members. However, the cooperative faces significant challenges due to its reliance on conventional, archive-based systems for processing savings transactions, loans, installments, and report preparation. These outdated methods result in time-consuming data searches and inefficiencies. To address this issue, the aim of this study is to develop a more efficient and computerized savings and loan information system for the Plasma Pratama Mandiri Cooperative. The study employs the Web Engineering method, encompassing stages such as communication, planning, modeling, construction, and deployment, with system modeling conducted using the Unified Modeling Language (UML). The outcome of this research is the development of an Android-based savings and loan information system for cooperative members and a web-based system for cooperative administrators. This new system facilitates online management and significantly enhances service efficiency for cooperative members.